Plotinus and art - Roome, J W (Rhodes University, Faculty of Humanities, Department of Fine Art, 1975)
Plotinua was the last great philosopher of Antiquity. He has greatly influenced philosophy, theology, mysticism and art. He became the guiding force of thought in the west. Because of his stress on the autonomy of spirit he is a precursor of modern times. He was the founder of speculative mysticism which deals with states and stages of union with the absolute. Chap. 1, p. 1.
Keywords: Plotinus